Implementasi Metode Jigsaw pada Mata Pelajaran IPS Kelas 4 di Sekolah Dasar - Susanto, Hendi; Widianto, Suheri (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research describes the implementation of the jigsaw method in social studies learning for grade IV elementary schools, the supporting and inhibiting factors in implementing the jigsaw method in social studies learning for grade IV elementary schools. The type of research used is a case study with a qualitative approach. Data collection techniques are interviews, observation and documentation. The Miles and Huberman model data analysis technique which includes data reduction, data presentation, and data verification. The results of the research show that the implementation of the jigsaw method in social studies learning in grade IV elementary school. Starting with the preparation of learning tools such as lesson plans. The teacher carries out the implementation process in learning, including initial or opening activities, core activities and final activities. The initial activities were carried out by the teacher by providing motivation and apperception. In the core activity, the teacher implements the Jigsaw method through the steps that have been prepared. In the final activity, the teacher provides a conclusion. The evaluation process is carried out through written tests. The results show effectiveness in the learning process and are able to improve learning outcomes for students.